Distraction versus training attention away from threat: How to best wait for the dentist?. (11th May 2016) - Horovitz, Omer; Roitburd, Brachali; Abend, Rany; Ziskind, Daniel; Shechner, Tomer
Abstract: Objective: Attention Bias Modification Training (ABMT) is a promising novel treatment for anxiety disorders. However, no randomised controlled trial has examined ABMT effects on anxiety in a real‐world fear‐provoking context. The current study examined the immediate effects of ABMT in reducing state anxiety among healthy participants awaiting dental treatment. Method: Seventy‐one healthy participants seeking treatment in a dental clinic were randomly assigned to either (1) Dental ABMT; (2) Attention Control Condition (ACC); or (3) Neutral Distraction. The study used a modified dot‐probe task consisting of dental and neutral words. In the ABMT condition, participants were trained to shift attention away from the dental words, whereas in the ACC, the same stimuli were presented, but attention was not trained in any specific direction. The Neutral Distraction task consisted of a casual video game. State anxiety was measured before and after completing the tasks while in the dentist's waiting room and immediately following the dental treatment. Results: Results indicated a significant interaction between time and condition on anxiety levels. The Neutral Distraction group showed a significant reduction in anxiety levels from pre‐ to post‐task (before dental treatment), but neither the ABMT nor the ACC group showed this trend. Following dental treatment, only the ACC group demonstrated a decrease in anxiety levels, while no change was reported by either the ABMT or the Neutral Distraction group. Conclusion: Findings from this exploratory study suggest that distraction tasks have a better immediate effect than ABMT in alleviating state anxiety in non‐anxious individuals who are expecting a relatively unpleasant experience.